Engineered column treatment of greywater using raw and pyrolyzed coconut husk powder - Taylor, Theodora Sophia; Appiah-Effah, Eugene; Akodwaa-Boadi, Kofi; Obeng, Ernest; Ofei-Quartey, Muriel Naa Lamiokor (Frontiers in Environmental Science, 2023)
This study explores the potential of coconut husk biomass, a common waste material in Ghana, as a valuable low-cost resource for greywater treatment. Engineered column treatment was applied to investigate the influence of pyrolysis and biochar properties of coconut husk biomass waste on greywater treatment. Coconut husk biomass waste was pyrolyzed at 600 oC and characterized using SEM, FTIR, and XRD. The SEM image suggested an increased surface area and pores due to the pyrolysis of the husk biomass. Three engineered columns with (1) raw coconut husk powder (RCHP), (2) charred coconut husk powder (CCHP), and (3) sand-gravel filters were used. A hydrostatic head of greywater with a throughput of 8.0 ml/min and a hydraulic retention time of 45 min was maintained for engineered columns. Significant differences were observed between CCHP and RCHP, p < 0.05 for electrical conductivity and total dissolved solids of effluents. Both RCHP and CCHP contributed to 63 % and 95 % turbidity removal, respectively. Experimental results showed high removal efficiencies of 71 % COD for CCHP. Nitrate removal efficiency of 78.93 %, 88.38 %, and 28.65 % was observed for RCHP, CCHP, and control respectively. The log removal of faecal coliform by CCHP was two orders of magnitude higher than RCHP. Faecal and total coliform removal was 2.87 log units for CCHP. CCHP showed a promising potential for greywater treatment.